Catalytic cracking catalyst as well as preparation method and application thereof
By controlling the load depth of rare earth metals on the catalyst surface, the problem of poor metal resistance of catalytic cracking catalysts is solved, and the catalyst has achieved the effect of low dry gas and hydrogen methane ratio, low hydrogen yield, high gasoline yield and high conversion rate when treating heavy oil containing contaminated metals such as Ni and V.
Patent Information
- Application Number
- CN202311445106.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-01
- Publication Date
- 2025-05-06
AI Technical Summary
When existing catalytic cracking catalysts treat heavy oils containing contaminated metals such as Ni and V, they have poor metal resistance, resulting in a high dry gas to hydrogen methane ratio, high hydrogen yield, low gasoline yield and low conversion rate.
By controlling the load depth of rare earth metal on the catalyst surface and preventing it from entering the internal pores of the catalyst particles, EPMA is used for linear analysis to ensure that the average load depth of rare earth metal components does not exceed 25% of the radius of the catalyst particles, and the utilization rate and metal resistance of rare earth metals are improved through organic matter adsorption and heat treatment methods.
The excellent metal resistance of the catalytic cracking catalyst is achieved. When containing contaminated metals such as Ni and V, the dry gas and hydrogen methane ratio is reduced. The hydrogen yield is low, the gasoline yield is high, and the conversion rate is high, which avoids the increase in the catalyst coking trend and the increase in the coke yield.
Smart Images

Figure CN119926479A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalysts, and in particular to a catalytic cracking catalyst and a preparation method and application thereof. Background Art
[0002] Fluid catalytic cracking (FCC) technology has become an important means of secondary processing of heavy oil in the world today because of its low investment, strong adaptability to raw materials and simple operation, and catalytic cracking catalyst plays a key role in this process. With the increasing depletion of high-quality light crude oil resources worldwide and the increase in delayed coking capacity, refineries have been blending a large proportion of low-quality crude oil such as residual oil, coking wax oil and deasphalted oil in catalytic cracking units in order to increase efficiency, which has a serious impact on the stable operation of catalytic cracking units and the distribution of cracking products, and has put forward higher requirements on the performance of catalytic cracking catalysts.
[0003] Since residual oil feed usually contains pollutant metals such as Ni, V, Fe, Na, and Ca, heavy metals such as nickel and vanadium in the feed oil are continuously deposited on the catalyst surface during the use of the catalytic cracking catalyst, causing certain toxic effects on the catalyst, and Ni has the greatest impact on the selectivity of the reaction. With the increase of the Ni content of the catalyst in the catalytic cracking unit, it shows a strong catalytic dehydrogenation effect, the hydrogen coke yield increases, and high-value products such as gasoline and LPG are affected. In addition, the high hydrogen yield will also cause the gas compressor to bear a large pressure. Various refineries at home and abroad have suppressed the dehydrogenation toxicity of this part of "active nickel" by adding a passivating Ni agent during the reaction. The passivating Ni agent is often injected into the cracking reactor in an oil-soluble or water-soluble liquid state. During the reaction, its effective components contact the catalyst surface and act on the "active nickel" on the catalyst surface to make it lose its toxicity. Since antimony has the best passivation effect on nickel toxicity, the most commonly used antimony-type metal passivator in China is currently antimony-type metal passivator. Studies have shown that antimony and reduced nickel form stable nickel antimonite NiSb x O y , thereby changing the electronic properties of Ni and thus passivating the Ni dehydrogenation activity.
[0004] However, a survey of waste catalysts produced by 40 catalytic cracking units across the country found that when antimony-type nickel passivation agents were added to the catalytic cracking units, the leaching toxicity of antimony metal in the catalytic cracking waste catalysts exceeded the Class III standard limit of the "Surface Water Quality Standard" (GB / T14848-2017) * 100 antimony 0.5 mg / L, which is the main factor causing catalytic cracking waste catalysts to have certain environmental risks. Therefore, in the face of increasingly stringent environmental protection requirements, preparing catalysts with high nickel tolerance and passivating the active nickel on the catalyst surface without using highly toxic antimony Sb is an important means to reduce hazardous waste at the source.
[0005] US5064524A discloses the use of cerium or cerium-containing compounds together with hydrocarbon feedstocks to suppress the adverse effects of nickel in cracking reactions. US5001096A discloses a surface coating process for discrete catalytic cracking catalyst particles, wherein the surface coating material consists of rare earth oxides, aluminum oxide and aluminum phosphate. However, this surface coating is weakly bonded to the base FCC catalyst and gradually peels off as the catalyst circulates in the FCC unit. WO2012004806A1 discloses a method for impregnating a lanthanum oxide-based solution on a base catalyst composite mixture by wet impregnation.
[0006] Although the existing research has found that rare earths such as La and Ce have an anti-metal effect, since the contaminated nickel is mainly distributed in the outermost layer of the catalytic cracking catalyst, the rare earths located in discrete particles, or the rare earths introduced directly in the catalyst matrix, or during the pulping process, are mostly inside the particles and cannot play a corresponding anti-nickel role, and the hydrogen and methane content of the cracking products is relatively high. In addition, the rare earths introduced by direct pulping or impregnation are easy to enter the micropores of the molecular sieve, which will increase the tendency of the catalyst to produce coke and increase the coke yield. Summary of the invention
[0007] The purpose of the present invention is to overcome the problems of poor metal resistance of catalytic cracking catalysts in the prior art and high hydrogen-methane ratio of cracking products, and to provide a catalytic cracking catalyst and a preparation method and application thereof. The catalytic cracking catalyst has excellent metal resistance and high catalytic cracking activity.
[0008] In order to achieve the above object, the present invention provides a catalytic cracking catalyst, which includes a catalyst substrate and a rare earth metal component supported on the catalyst substrate;
[0009] The catalyst matrix includes molecular sieve, clay and binder;
[0010] Wherein, the cross section of the catalyst particles is subjected to line analysis using EPMA, and the average loading depth of the rare earth metal component does not exceed 25% of the radius of the catalyst particles.
[0011] A second aspect of the present invention provides a method for preparing a catalytic cracking catalyst, comprising:
[0012] (1) contacting the catalyst substrate with organic matter to adsorb the organic matter into the pores of the catalyst substrate;
[0013] Wherein, the boiling point of the organic matter is 100-250°C; the catalyst matrix includes molecular sieve, clay and binder;
[0014] (2) introducing a rare earth metal component into the product obtained in step (1);
[0015] (3) Removing organic matter from the product obtained in step (2).
[0016] The third aspect of the present invention provides a catalytic cracking catalyst prepared by the above preparation method.
[0017] The fourth aspect of the present invention provides use of the catalytic cracking catalyst described in the first aspect and the third aspect in a catalytic cracking reaction of heavy oil.
[0018] The inventors of the present invention have found in their research that by controlling the loading depth of rare earth metals on the catalyst surface and preventing rare earth elements from entering the internal pores of catalyst particles, it is more conducive to exerting the anti-metal effect of rare earth metals, while being able to avoid an increase in the tendency of catalyst coking and reduce the coke yield. The catalytic cracking catalyst provided by the present invention has excellent anti-metal ability, has a lower dry gas and hydrogen-methane ratio when containing contaminated metals such as Ni and V, has a lower hydrogen yield, and has a high gasoline yield and a high conversion rate.
[0019] The preparation method of the catalytic cracking catalyst provided by the present invention comprises the following steps: firstly adsorbing organic matter on the catalyst substrate, and then adsorbing the organic matter into the micropores and mesopores of the catalyst substrate; then loading the rare earth metal component in a conventional manner; and then removing the organic matter by heat treatment or vacuum desorption, thereby reducing the entry of the rare earth metal into the micropores or mesopores as much as possible, effectively controlling the loading depth of the catalyst surface, and thus improving the utilization rate of the rare earth metal and the anti-metal ability. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a cross-sectional element electron probe microanalysis picture of the catalytic cracking catalyst C1 prepared in Example 1 of the present invention;
[0021] Figure 2 It is an element line scan distribution diagram of the cross section of the catalytic cracking catalyst C1 prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0022] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0023] A first aspect of the present invention provides a catalytic cracking catalyst, the catalyst comprising a catalyst substrate and a rare earth metal component supported on the catalyst substrate;
[0024] The catalyst matrix includes molecular sieve, clay and binder;
[0025] Wherein, the cross section of the catalyst particles is subjected to line analysis using EPMA, and the average loading depth of the rare earth metal component does not exceed 25% of the radius of the catalyst particles.
[0026] The catalytic cracking catalyst provided by the present invention has excellent metal resistance, has a lower dry gas and hydrogen-methane ratio in the case of containing contaminated metals such as Ni and V, has a low hydrogen yield, and has a high gasoline yield and a high conversion rate. The reason is that the loading depth of the rare earth metal component is controlled mainly in the surface layer, which is more conducive to exerting the anti-metal effect of the rare earth metal, and can also avoid the increase of the catalyst coking tendency and reduce the coke yield. Preferably, the profile of the catalyst particles is analyzed by EPMA, and the average loading depth of the rare earth metal component is 1-25% of the catalyst particle radius, preferably 5-20%.
[0027] In the present invention, the loading depth of the rare earth metal component is tested by the following method:
[0028] The catalyst particles are observed using EPMA, and the field of view is adjusted to have 10-50 catalyst particles. Any catalyst particle is selected, and along any radial direction of the particle, the ratio of the distance from the outer edge of the particle cross section to the position where the rare earth metal component content reaches 80wt% of the total loading on the radius to the particle radius is recorded as the loading depth of the rare earth metal component on the radius. Four different radii are selected from each particle for element line scanning distribution statistics of loading depths, and the average value is calculated and recorded as the loading depth of the rare earth metal component in the catalyst particle; then, the loading depths of the rare earth metal components in five different catalyst particles within the field of view are statistically calculated according to the above method, and recorded as the average loading depth of the rare earth metal component in the catalyst.
[0029] According to the present invention, preferably, in the catalytic cracking catalyst, the average particle size of the rare earth metal component does not exceed 10nm, preferably does not exceed 5nm. Within the above preferred range, it is shown that the rare earth metal component has good dispersibility on the surface of the catalyst substrate, and by controlling the loading depth and high dispersity of the rare earth metal component, it is beneficial to further improve the catalytic activity and metal resistance of the catalytic cracking catalyst. If the particle clusters are too large, it is not conducive to improving the capacity for nickel and reducing the hydrogen-methane ratio.
[0030] In the present invention, the average particle size of the rare earth metal component is statistically obtained by transmission electron microscopy (mapping) testing method.
[0031] According to some preferred embodiments of the present invention, the total pore volume of the catalyst is 0.2-0.6 mL / g, preferably 0.25-0.5 mL / g.
[0032] Preferably, in the catalyst, the pore volume of micropores and mesopores accounts for 60-98% of the total pore volume, preferably 70-90%; the pore volume of macropores accounts for 2-40% of the total pore volume, preferably 10-30%. In the above preferred case, it is beneficial to the diffusion of catalytic cracking reaction and the effective distribution of active centers, further improving the catalytic cracking activity of the catalyst.
[0033] In the present invention, micropores, mesopores and macropores have the conventional definitions in the art, "micropores" refer to pores with a pore diameter less than 2 nm; "mesopores" refer to pores with a pore diameter between 2-50 nm; and "macroporos" refer to pores with a pore diameter greater than 50 nm.
[0034] In the present invention, the total pore volume and pore distribution of the catalyst are measured by the BET method.
[0035] All rare earth metals that are resistant to metals such as Ni and V can be applied to the present invention. Preferably, the rare earth metal component is selected from La and / or Ce, preferably La. In the above preferred case, it is beneficial to further improve the metal resistance of the catalytic cracking catalyst.
[0036] Preferably, based on the total amount of the catalyst, the content of the rare earth metal component is 0.3-5wt%, preferably 0.5-4wt%, calculated as oxide; the content of the catalyst matrix is 95-99.7wt%, preferably 96-99.5wt%. Controlling the content of the rare earth metal component within the above preferred range is conducive to controlling the dispersion and depth of the loaded metal and maintaining a good surface area, and is conducive to the catalytic cracking catalyst having both high catalytic cracking activity and resistance to contaminating metals such as Ni and V.
[0037] In the present invention, the content of the rare earth metal component is obtained by X-ray fluorescence spectroscopy (XRF) testing.
[0038] The present invention has no particular requirements for the specific composition of the catalyst substrate, and any catalyst substrate with catalytic cracking activity known in the art can be applied to the present invention. Through the synergistic effect of the catalyst substrate with catalytic cracking activity and the rare earth metal component on the surface, the ability to resist contaminating metals such as Ni and V can be improved while ensuring the catalytic cracking activity.
[0039] According to some preferred embodiments of the present invention, based on the total amount of the catalyst substrate, the content of the molecular sieve is 10-65wt%, preferably 15-50wt%; the content of the clay is 5-45wt%, preferably 10-40wt%; the content of the binder is 10-50wt%, preferably 10-30wt%.
[0040] The present invention has a wide range of selection for the specific type of the molecular sieve. Preferably, the molecular sieve is selected from at least one of a Y-type molecular sieve, a beta molecular sieve and an MFI molecular sieve, preferably a Y-type molecular sieve. The present invention has no special requirements for the source of the molecular sieve, which can be purchased from a commercial source, for example, the Y-type molecular sieve can be a DASY.2.0 molecular sieve purchased from the Qilu Branch of Sinopec Catalyst Co., Ltd.; it can also be prepared by any method known in the art.
[0041] Preferably, the molar ratio of silicon oxide to aluminum oxide in the molecular sieve is 3-80, preferably 10-50.
[0042] The present invention has a wide range of clays to choose from, and clays conventionally defined in the art are applicable to the present invention. Preferably, the clay is selected from at least one of kaolin, bentonite, montmorillonite, sepiolite and diatomaceous earth, preferably kaolin.
[0043] In the present invention, there is no particular limitation on the specific type of the binder, and any binder conventionally defined in the art can be applied to the present invention. Preferably, the binder is aluminum oxide and / or silicon oxide.
[0044] A second aspect of the present invention provides a method for preparing a catalytic cracking catalyst, comprising:
[0045] (1) contacting the catalyst substrate with organic matter to adsorb the organic matter into the pores of the catalyst substrate;
[0046] Wherein, the boiling point of the organic matter is 100-250°C; the catalyst matrix includes molecular sieve, clay and binder;
[0047] (2) introducing a rare earth metal component into the product obtained in step (1);
[0048] (3) Removing organic matter from the product obtained in step (2).
[0049] In the catalytic cracking catalyst prepared by the above preparation method, the profile of the catalyst particles is analyzed by EPMA, and the average loading depth of the rare earth metal component does not exceed 25% of the radius of the catalyst particles, preferably 1-25%, more preferably 5-20%.
[0050] According to the present invention, the boiling point of the organic matter is 100-250°C, for example, it can be 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, etc., typical but not limiting boiling points or ranges between the two. Adsorption of organic matter within the above boiling point range, on the one hand, the organic matter has a suitable molecular weight and volume size, which is conducive to adsorbing the organic matter into the pores of the catalyst matrix, thereby helping to control the loading depth of the catalyst surface; on the other hand, within the above boiling point range, the organic matter can be removed at a relatively low heat treatment temperature, thereby helping to improve the loading effect of the catalyst surface. Preferably, the boiling point of the organic matter is 110-200°C. The use of the above preferred embodiment is conducive to further improving the rare earth metal loading effect on the catalyst surface and improving the utilization rate of rare earth metals.
[0051] The present invention has a wide range of selection for the specific type of the organic matter, as long as it meets the above boiling point range. The organic matter can be a hydrocarbon, and can also contain heteroatoms such as S, P or N, and the present invention has no special limitation on this.
[0052] According to some preferred embodiments of the present invention, the organic matter is selected from substituted or unsubstituted aromatic hydrocarbons and / or alkanes, and optionally, at least one carbon atom in the aromatic hydrocarbons or alkanes is substituted by S, P or N. The substituent in the substituted aromatic hydrocarbons or alkanes may be, for example, methyl and / or ethyl.
[0053] Preferably, the organic matter is selected from at least one of benzene, toluene, ethylbenzene, xylene, trimethylbenzene, trimethylphosphine, picoline and colloidal pyridine. It is understood that the organic matter listed above also includes any isomers thereof, for example, xylene includes o-xylene, m-xylene and p-xylene, which are well known to those skilled in the art. The above preferred embodiment is used to further reduce the entry of rare earth metals into the catalyst particles and improve the utilization rate of rare earth metals.
[0054] In a further preferred embodiment, the organic matter is selected from at least one of toluene, xylene and ethylbenzene.
[0055] The present invention has a wide selection range for the adsorption amount of the organic matter. It can be understood that in the present invention, the loading depth of the rare earth metal component can be further controlled by controlling the adsorption amount of the organic matter. Those skilled in the art can make adjustments according to the actual needs of the catalyst.
[0056] According to some preferred embodiments of the present invention, based on the water droplet pore volume of the catalyst substrate, the adsorption amount of the organic matter is 40-95 vol%, preferably 60-90 vol%. Controlling the adsorption amount of the organic matter within the above range is conducive to the controllable distribution depth dispersion of the loaded metal.
[0057] In the present invention, the water droplet pore volume of the micron-sized catalyst substrate particles is measured by the water drop method for determining the pore volume of catalytic cracking catalysts in NB / SH / T0955-2017. The catalyst substrate particles of millimeter size and above can be measured by combining the macropore volume measured by mercury intrusion and the micropore volume measured by BET method.
[0058] In the present invention, the contacting in step (1) can be carried out under vacuum conditions or non-vacuum conditions. Preferably, the contacting in step (1) is carried out under vacuum conditions. Preferably, the vacuum conditions include: an absolute pressure of 1×10 -5 Pa to 10 Pa. The above preferred implementation is advantageous for the organic material to first fill the micropores and mesopores, and then gradually diffuse from the mesopores to the macropores, and the pore filling is distributed in a step-like manner.
[0059] According to some preferred embodiments of the present invention, the contacting method in step (1) includes: contacting the atmosphere containing organic matter with the catalyst substrate under vacuum conditions. Specifically, the catalyst substrate can be first vacuumized, and then the atmosphere containing organic matter is introduced to adsorb the organic matter into the pores of the catalyst substrate, which is beneficial to improve the adsorption uniformity of the organic matter, further increase the relatively uniform loading depth of the rare earth metal component, and improve the metal resistance of the catalyst.
[0060] The present invention has no particular limitation on the specific method of introducing the rare earth metal component in step (2), and it can be carried out by conventional loading methods in the art, such as impregnation or spraying.
[0061] According to some preferred embodiments of the present invention, the method of introducing the rare earth metal component into the product obtained in step (1) comprises: impregnating or spraying a solution containing a rare earth metal precursor onto the product obtained in step (1), and then drying. The above preferred embodiments are advantageous for further improving the dispersion of the rare earth metal component and reducing particle clusters, thereby further improving the catalytic activity and metal resistance of the catalytic cracking catalyst.
[0062] The inventors of the present invention further discovered that although the co-precipitation method can also control the average loading depth of the rare earth metal component, the metal particles are easy to agglomerate and the particle size is large, which is not conducive to the nickel accommodation capacity and is not conducive to reducing the hydrogen-methane ratio.
[0063] Preferably, the drying includes a low-temperature drying stage and a high-temperature drying stage, wherein the temperature of the low-temperature drying stage is 80-110°C, the time is 1-100min, and the heating rate is 1-20°C / min; the temperature of the high-temperature drying stage is 110-250°C, the time is 10-120min, and the heating rate is 1-20°C / min. The above preferred embodiment is adopted, through slow heating and stage drying, which is conducive to the stable fixation of the rare earth metal component on the surface of the catalyst substrate, reducing the rare earth metal component from entering the pores of the catalyst substrate, thereby further improving the utilization rate of the rare earth metal component and improving the metal resistance of the prepared catalytic cracking catalyst.
[0064] Preferably, the drying is performed under an inert atmosphere, which is preferably provided by nitrogen.
[0065] The present invention has no particular limitation on the selection of the rare earth metal precursor, and a soluble compound of a rare earth metal may be used, such as chloride, nitrate, oxalate, sulfate, etc. The present invention has no particular limitation on the concentration of the solution containing the rare earth metal precursor, and preferably, the concentration of the solution containing the rare earth metal precursor is 1-30wt%.
[0066] According to the present invention, the solution containing the rare earth metal precursor also contains a solvent. Preferably, the boiling point of the solvent in the solution containing the rare earth metal precursor is lower than the boiling point of the organic matter. In the above preferred case, it is beneficial to control the loading depth of the rare earth metal, ensure that the rare earth metal is preferentially loaded on the outer surface and part of the macropore surface, and reduce the entry into the mesopores and micropores; preferably, the boiling point of the solvent in the solution containing the rare earth metal precursor is 10-150°C lower than the boiling point of the organic matter.
[0067] According to the present invention, preferably, at 25°C, the solubility of the solvent in the solution containing the rare earth metal precursor in 100g of organic matter is not higher than 0.5g, preferably not higher than 0.1g; in the above preferred case, it is beneficial to improve the utilization rate of the rare earth metal component and avoid component loss.
[0068] All rare earth metals that are resistant to metals such as Ni and V can be applied to the present invention. Preferably, the rare earth metal component is selected from La and / or Ce, preferably La.
[0069] Preferably, the amount of solution containing rare earth metal precursor is such that, based on the total amount of the catalyst, the content of the rare earth metal component is 0.3-5wt%, preferably 0.5-4wt% in terms of oxide; the content of the catalyst matrix is 95-99.7wt%, preferably 96-99.5wt%.
[0070] In the present invention, the content of each component in the catalyst is determined by X-ray fluorescence (XRF).
[0071] The present invention has no particular requirements for the specific method of removing the organic matter in the product obtained in step (2) in step (3). For example, the organic matter can be removed by heat treatment or vacuum desorption.
[0072] According to some preferred embodiments of the present invention, the heat treatment conditions include: temperature of 200-500° C., preferably 250-450° C.; time of 10-180 min, preferably 30-120 min.
[0073] According to some preferred embodiments of the present invention, the vacuum desorption conditions include: an absolute pressure of 1×10 - 5 Pa to 10Pa, preferably 1×10 -4 Pa to 0.1 Pa; the temperature of vacuum desorption is 20-30°C, preferably at room temperature.
[0074] The use of the above preferred embodiment to remove organic matter from the product obtained in step (2) is beneficial to improving the removal efficiency of organic matter and avoiding the loss of loaded components.
[0075] In the present invention, the catalyst substrate has the same definition and composition range as the first aspect, which will not be repeated here. The present invention has no particular limitation on the source of the catalyst substrate, and a commercially available catalytic cracking catalyst can be used, or it can be prepared by methods known in the art.
[0076] According to some preferred embodiments of the present invention, the method for preparing the catalyst substrate comprises:
[0077] The molecular sieve, clay and binder precursor are mixed, molded and calcined, and then the obtained solid product is treated with alkali.
[0078] In the present invention, the binder precursor refers to any substance that can be calcined to obtain the binder, which is well known to those skilled in the art. For example, the precursor of aluminum oxide can be at least one of aluminum sol, pseudo-boehmite and acidified pseudo-boehmite, and the precursor of silicon oxide can be silica sol.
[0079] The acidified pseudo-boehmite can be obtained by contacting the pseudo-boehmite with an acid solution for acidification treatment, which is well known to those skilled in the art.
[0080] According to some preferred embodiments of the present invention, the binder precursor comprises acidified pseudo-boehmite and alumina sol. On a dry basis, the mass ratio of the acidified pseudo-boehmite to the alumina sol is preferably (1-10):1.
[0081] The present invention has no special requirements for the molding method, and can be carried out by conventional catalyst molding methods in the art, such as spray drying molding. The present invention has no special requirements for the specific operation method and conditions of the spray drying, as long as the above molding process can be achieved.
[0082] Preferably, the calcination temperature is 400-600° C. and the calcination time is 0.5-8 h.
[0083] In the present invention, the solid product after forming and calcining is subjected to alkali treatment to form protonic acid through ion exchange, thereby increasing the active centers of the catalytic cracking catalyst.
[0084] According to some preferred embodiments of the present invention, the alkali treatment method comprises: rinsing the solid product with an alkaline solution and then drying. The present invention does not particularly limit the number of rinsing times, and those skilled in the art can select according to actual needs. Preferably, the number of rinsing times is 1-3 times. The alkali treatment can be carried out at room temperature, and in the present invention, room temperature refers to 25°C ± 5°C.
[0085] The present invention has a wide selection range for the alkaline solution. Preferably, the alkaline solution is a non-metallic element alkaline solution, and more preferably, it is ammonia water and / or an ammonium salt solution. The ammonium salt solution may be, for example, an ammonium chloride solution.
[0086] The present invention has a wide selection range for the concentration and dosage of the alkaline solution. For example, the concentration of the alkaline solution can be 1-10 wt %, preferably 1-5 wt %.
[0087] Preferably, the drying conditions include: temperature of 80-150° C. and time of 30-120 h.
[0088] The third aspect of the present invention provides a catalytic cracking catalyst prepared by the above preparation method.
[0089] The catalyst comprises a catalyst matrix and a rare earth metal component loaded on the catalyst matrix; the catalyst matrix comprises a molecular sieve, clay and a binder; wherein, by performing line analysis on the profile of the catalyst particles using EPMA, the average loading depth of the rare earth metal component does not exceed 25% of the radius of the catalyst particles, is preferably 1-25%, and more preferably 5-20%.
[0090] The fourth aspect of the present invention provides use of the catalytic cracking catalyst described in the first aspect and the third aspect in a catalytic cracking reaction of heavy oil.
[0091] In particular, it is used in the catalytic cracking reaction of heavy oil containing pollutant metals such as Ni, V, Fe, Na, Ca, etc.
[0092] The present invention will be described in detail below through examples.
[0093] Unless otherwise specified, the raw materials used in the following examples and comparative examples are commercially available.
[0094] Example 1
[0095] (1) Take 20 parts by mass of pseudo-boehmite (on a dry basis, a product of Shandong Aluminum Company), acidify it and then slurry it to prepare an acidified boehmite with a solid content of 12% by mass; then add 10 parts by mass of aluminum sol (on a dry basis), 34 parts by mass of kaolin (on a dry basis) and 36 parts by mass (on a dry basis) of DASY.2.0 molecular sieve (a product of Qilu Branch of Sinopec Catalyst Co., Ltd., with a molar ratio of silicon oxide to aluminum oxide of 10.8), stir for 0.5 h, spray dry, calcine at 550°C for 2 h, wash it twice with a 2% by mass ammonium chloride solution, and dry it at 120°C for 2 h to obtain a catalyst matrix Cat-A.
[0096] (2) A 30 mL vacuum treatment reactor is used, wherein the vacuum treatment reactor is a sealable quartz chamber, wherein a connecting valve A is connected to a vacuum pump, another connecting valve B is connected to a xylene storage tube, and there is also a vent valve C.
[0097] Place 10 g of Cat-A (dry basis) in a 30 mL vacuum reactor, close the vent valve and connector B, open connector A, turn on the vacuum pump, and perform vacuum treatment. When the absolute pressure reaches 10 -3 Pa, close valve A and then slowly open valve B. When the xylene in the xylene storage tank is reduced by about 3 mL through volatilization under vacuum, the adsorption amount of xylene is about 75 vol% of the water droplet pore volume of the catalyst matrix, and then close valve B.
[0098] (3) All the products after adsorption of xylene were placed in 10 mL of lanthanum chloride solution with 5 wt% of lanthanum oxide and manually stirred for 20 min, then filtered, and then slowly dried under a nitrogen atmosphere. The temperature was set to rise from 60°C to 100°C after 60 min and kept at this temperature for 30 min to fully dry, and then raised to 150°C after 30 min and kept at this temperature for 30 min (the gas was promptly removed). Then the temperature was raised to 400°C for heat treatment for 30 min. Catalytic cracking catalyst C1 was obtained, and the loading amount of lanthanum oxide was about 2 wt%.
[0099] The La element electron probe microanalysis picture of C1 is shown in Figure 1 , and the element line scan distribution of a single particle section is shown in Figure 2It can be seen that the La-loaded metal is preferentially distributed on the outer surface of the catalyst. The physical and chemical properties of the catalyst are shown in Table 1. The particle size of lanthanum oxide particles was counted by transmission electron microscopy. It can be seen that the particle size of lanthanum oxide particles on the outer surface of the catalyst is mostly less than 1nm, and there are very few cluster particles. The average particle size of the cluster particles is about 4nm.
[0100] Example 2
[0101] The catalyst substrate Cat-A prepared in Example 1 was used. 10 g of Cat-A (dry basis) was placed in a 30 mL vacuum reactor. After closing the vent valve and connector B, connector A was opened and the vacuum pump was turned on for vacuum treatment. When the absolute pressure reached 10 -3 When the xylene in the xylene storage tank decreases by about 1.8 mL by volatilization under vacuum, valve B is closed. At this time, the adsorption amount of xylene is about 45 vol% of the water droplet pore volume of the catalyst matrix.
[0102] Then, lanthanum oxide was loaded according to the method of Example 1 to obtain a catalytic cracking catalyst C2 with a lanthanum oxide loading of about 3.5 wt%. The physical and chemical properties of the catalyst are shown in Table 1. The particle size of the lanthanum oxide particles was counted by transmission electron microscopy, and it can be seen that the particle size of the lanthanum oxide particles on the outer surface of the catalyst is mostly less than 1 nm, and there are very few cluster particles, and the average particle size of the cluster particles is about 5 nm.
[0103] Example 3
[0104] The catalyst substrate Cat-A prepared in Example 1 was used. 10 g of Cat-A (dry basis) was placed in a 30 mL vacuum reactor. After closing the vent valve and connector B, connector A was opened and the vacuum pump was turned on for vacuum treatment. When the absolute pressure reached 10 -5 When the xylene in the xylene storage tank decreases by about 3.4 mL by volatilization under vacuum, valve B is closed. At this time, the adsorption amount of xylene is about 85 vol% of the water droplet pore volume of the catalyst matrix.
[0105] Then, lanthanum oxide was loaded according to the method of Example 1 to obtain a catalytic cracking catalyst C3 with a lanthanum oxide loading of about 1.5 wt%. The physical and chemical properties of the catalyst are shown in Table 1. The particle size of lanthanum oxide particles was counted by transmission electron microscopy, and it can be seen that the particle size of lanthanum oxide particles on the outer surface of the catalyst is mostly less than 1 nm, and there are very few cluster particles, and the average particle size of the cluster particles is about 2 nm.
[0106] Example 4
[0107] The method of Example 1 is followed, except that step (2) does not involve vacuuming.
[0108] 3 mL of xylene was added dropwise into 10 g of Cat-A (dry basis) while being continuously stirred to obtain a catalytic cracking catalyst that adsorbed xylene.
[0109] Then, lanthanum oxide was loaded according to the method of Example 1 to obtain a catalytic cracking catalyst C4 with a lanthanum oxide loading of about 2.8 wt%. The physical and chemical properties of the catalyst are shown in Table 1. The particle size of lanthanum oxide particles was counted by transmission electron microscopy, and it can be seen that the particle size of lanthanum oxide particles on the outer surface of the catalyst is mostly less than 1 nm, and there are very few cluster particles, and the average particle size of the cluster particles is about 8 nm.
[0110] Example 5
[0111] The method of Example 1 is the same, except that the drying conditions in step (2) include: setting the temperature program to rise from 60°C to 150°C after 120 minutes and keep warm for 30 minutes (the gas is promptly pumped away). Then the temperature is raised to 400°C and kept warm for 30 minutes. The catalyst with a lanthanum oxide loading of about 2wt% is recorded as C5, and the physicochemical properties of the catalyst are shown in Table 1. The particle size of the lanthanum oxide particles was counted by transmission electron microscopy, and it can be seen that the particle size of the lanthanum oxide particles on the outer surface of the catalyst is mostly less than 1nm, and there are very small amounts of clustered particles, and the average particle size of the clustered particles is about 3nm.
[0112] Example 6
[0113] The method of Example 1 is used, except that step (3) uses a spraying method to load lanthanum oxide, specifically comprising: spraying with a lanthanum chloride solution containing 5 wt% of lanthanum oxide, spraying 2 mL, slowly heating to 120°C in a nitrogen atmosphere for drying for 20 min, then spraying with 2 mL of lanthanum chloride solution, and then slowly drying in a nitrogen atmosphere (setting a program temperature rise from 60°C to 100°C after 60 min and keeping warm for 30 min to fully dry, then heating to 150°C in 30 min and keeping warm for 30 min (the gas is promptly removed). Then heating to 400°C and keeping warm for 30 min. A catalytic cracking catalyst C6 with a lanthanum oxide loading of about 2 wt% is obtained. The particle size of the lanthanum oxide particles is counted by transmission electron microscopy. It can be seen that the particle size of the lanthanum oxide particles on the outer surface of the catalyst is mostly less than 1 nm, and there are very few cluster particles. The average particle size of the cluster particles is about 7 nm.
[0114] Example 7
[0115] The catalyst substrate Cat-A prepared in Example 1 was used. 10 g of Cat-A (dry basis) was placed in a 30 mL vacuum reactor. After closing the vent valve and connector B, connector A was opened and the vacuum pump was turned on for vacuum treatment. When the absolute pressure reached 10 -3 When pa, valve A is closed, and then valve B is slowly opened. When the xylene in the xylene storage tank is reduced by about 0.8 mL by volatilization under vacuum, valve B is closed. At this time, the adsorption amount of xylene is about 20 vol% of the water droplet pore volume of the catalyst matrix.
[0116] Then, lanthanum oxide was loaded according to the method of Example 1 to obtain a catalytic cracking catalyst C2 with a lanthanum oxide loading of about 3.6 wt%. The physical and chemical properties of the catalyst are shown in Table 1. The particle size of lanthanum oxide particles was counted by transmission electron microscopy, and it can be seen that the particle size of lanthanum oxide particles on the outer surface of the catalyst is mostly less than 1 nm, and there are very few cluster particles, and the average particle size of the cluster particles is about 6 nm.
[0117] Comparative Example 1
[0118] The catalyst substrate Cat-A prepared in Example 1 was directly used as catalytic cracking catalyst D1.
[0119] Comparative Example 2
[0120] Take 18 parts by weight of pseudo-boehmite, acidify and then slurry to prepare acidified boehmite with a solid content of 12% by weight; then add 10 parts by weight of aluminum sol (dry basis), about 2 parts of lanthanum chloride solution based on lanthanum oxide, 33 parts by weight of kaolin (dry basis) and 36 parts by weight of DASY.2.0 molecular sieve (dry basis), stir for 0.5h and then spray dry, calcine at 550°C for 2h, wash twice with 2% by weight ammonium chloride solution, and obtain catalytic cracking catalyst microspheres with a lanthanum oxide content of about 2wt%, which are recorded as D2. The physical and chemical properties of the catalyst are shown in Table 1.
[0121] Comparative Example 3
[0122] The method of Example 1 was followed, except that no organic matter adsorption was performed, and 10 g of Cat-A was directly impregnated in step (3) to obtain a catalytic cracking catalyst D3 with a lanthanum oxide loading of about 4.4 wt%. The physicochemical properties of the catalyst are shown in Table 1.
[0123] Table 1
[0124]
[0125] Test Case
[0126] (1) Activity before contamination
[0127] The catalytic cracking catalysts prepared in Examples 1-3 and Comparative Example 1 were evaluated on an ACE D100 device. The ACE-evaluated feedstock oil properties are shown in Table 2, and the evaluation results are shown in Table 3.
[0128] (2) Activity after contamination
[0129] The catalytic cracking catalysts prepared in the above examples and comparative examples were respectively subjected to a circulating contamination method on an ACE D100 device, wherein nickel cyclopentaneate and vanadium cyclopentaneate were dissolved in distillate oil at a mass ratio of 5:2 and subjected to multiple cyclic reactions until the Ni content on the catalyst was about 4500 ppm (mass) and the V content was 1800 ppm (mass).
[0130] The samples after circulation contamination are numbered as C1w~C7w and D1w~D3w. The catalyst samples after circulation contamination were then aged for 12 hours at 100% steam in a fixed bed at 800°C, and then evaluated in an ACE fluidized bed device. The ACE evaluation feedstock properties are shown in Table 2, and the evaluation conditions and evaluation results are shown in Table 4 and Table 4.
[0131] Table 2
[0132]
[0133] Table 3
[0134]
[0135]
[0136] Table 4
[0137] Catalyst No. C1W C2 C3W C4w C5W C6W C7 Cracking reaction temperature,℃ 500 500 500 500 500 500 500 Agent to oil ratio, wt / wt 6 6 6 6 6 6 6 Yield wt%: Dry gas 1.66 1.68 1.74 1.69 1.68 1.69 1.71 hydrogen 0.11 0.09 0.12 0.14 0.13 0.13 0.15 Methane 0.6 0.64 0.59 0.59 0.64 0.61 0.56 Liquefied gas 16.64 16.57 16.78 16.53 16.49 16.64 16.34 Coke 8.71 8.95 8.93 8.94 8.87 8.71 9.23 gasoline 48.58 48.89 48.03 48.58 48.68 48.56 48.72 diesel fuel 16.32 15.95 16.38 16.05 16.04 16.31 16.37 heavy oil 8.09 7.96 8.14 8.21 8.24 8.09 7.63 Conversion rate, wt% 75.59 76.09 75.48 75.74 75.72 75.6 76 <![CDATA[N(H2) / n(CH4)]]> 1.47 1.13 1.63 1.90 1.63 1.70 2.14
[0138] Table 4
[0139] Catalyst No. 1x dW 3W Cracking reaction temperature,℃ 500 500 500 Agent-oil ratio, wt / wt 6 6 6 Yield wt%: Dry gas 1.78 1.67 1.72 hydrogen 0.27 0.25 0.21 Methane 0.6 0.58 0.59 Liquefied gas 16.89 16.42 16.21 Coke 8.86 9.07 9.31 gasoline 47.87 48.63 48.84 diesel fuel 16.67 16.56 16.36 heavy oil 7.93 7.65 7.56 Conversion rate, wt% 75.4 75.79 76.08 <![CDATA[n(H2) / n(CH4)]]> 3.60 3.45 2.85
[0140] Combining the results of Table 3, Table 4 and Table 4, it can be seen that the catalytic cracking catalyst prepared in the embodiment of the present invention has a high catalytic cracking activity, and can still have a low dry gas and hydrogen-methane ratio in the presence of contaminating metals such as Ni and V, and a low hydrogen yield, while having a high gasoline yield and a high conversion rate, indicating that the above catalytic cracking catalyst has excellent metal resistance. In contrast, the catalytic cracking catalyst prepared in the comparative example has a significantly reduced catalytic performance and weak metal resistance after metal contamination.
[0141] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A catalytic cracking catalyst, characterized in that: The catalyst comprises a catalyst substrate and a rare earth metal component supported on the catalyst substrate; The catalyst matrix includes molecular sieve, clay and binder; Wherein, the cross section of the catalyst particles is subjected to line analysis using EPMA, and the average loading depth of the rare earth metal component does not exceed 25% of the radius of the catalyst particles.
2. The catalyst according to claim 1, wherein The cross section of the catalyst particles is subjected to line analysis using EPMA, and the average loading depth of the rare earth metal component is 1-25% of the radius of the catalyst particles, preferably 5-20%; Preferably, the average particle size of the rare earth metal component is no more than 10 nm, preferably no more than 5 nm.
3. The catalyst according to claim 1 or 2, wherein The total pore volume of the catalyst is 0.2-0.6 mL / g, preferably 0.25-0.5 mL / g; Preferably, in the catalyst, the pore volume of micropores and mesopores accounts for 60-98% of the total pore volume, and the pore volume of macropores accounts for 2-40% of the total pore volume.
4. The catalyst according to any one of claims 1 to 3, wherein The rare earth metal component is selected from La and / or Ce, preferably La; Preferably, based on the total amount of the catalyst, the content of the rare earth metal component is 0.3-5wt%, preferably 0.5-4wt%, calculated as oxide; the content of the catalyst matrix is 95-99.7wt%, preferably 96-99.5wt%.
5. The catalyst according to any one of claims 1 to 4, wherein Based on the total amount of the catalyst matrix, the content of the molecular sieve is 10-65wt%, the content of the clay is 5-45wt%, and the content of the binder is 10-50wt%; Preferably, the molecular sieve is at least one of a Y-type molecular sieve, a beta molecular sieve and an MFI molecular sieve; Preferably, the molar ratio of silicon oxide to aluminum oxide in the molecular sieve is 3-80; Preferably, the clay is selected from at least one of kaolin, bentonite, montmorillonite, sepiolite and diatomaceous earth; Preferably, the binder is aluminum oxide and / or silicon oxide.
6. A method for preparing a catalytic cracking catalyst, comprising: (1) contacting the catalyst substrate with organic matter to adsorb the organic matter into the pores of the catalyst substrate; in, The boiling point of the organic matter is 100-250°C; the catalyst matrix includes molecular sieve, clay and binder; (2) introducing a rare earth metal component into the product obtained in step (1); (3) Removing organic matter from the product obtained in step (2).
7. The preparation method according to claim 6, wherein: The boiling point of the organic matter is 110-200°C; Preferably, the organic matter is selected from substituted or unsubstituted aromatic hydrocarbons and / or alkanes, and optionally, at least one carbon atom in the aromatic hydrocarbons or alkanes is substituted by S, P or N; Preferably, the organic matter is selected from at least one of benzene, toluene, ethylbenzene, xylene, trimethylbenzene, trimethylphosphine, picoline and coltidine; Preferably, based on the water droplet pore volume of the catalyst matrix, the adsorption amount of the organic matter is 40-95 vol%, preferably 60-90 vol%.
8. The preparation method according to claim 6 or 7, wherein: The contacting in step (1) is carried out under vacuum conditions. Preferably, the vacuum conditions include: an absolute pressure of 1×10 -5 Pa to 10Pa; Preferably, the contacting method in step (1) comprises: contacting an atmosphere containing organic matter with the catalyst substrate under vacuum conditions.
9. The preparation method according to any one of claims 6 to 8, wherein: In step (2), the method of introducing the rare earth metal component into the product obtained in step (1) includes: impregnating or spraying a solution containing a rare earth metal precursor onto the product obtained in step (1), and then drying; Preferably, the drying includes a low-temperature drying stage and a high-temperature drying stage, wherein the temperature of the low-temperature drying stage is 80-110°C, the time is 1-100 min, and the heating rate is 1-20°C / min; the temperature of the high-temperature drying stage is 110-250°C, the time is 10-120 min, and the heating rate is 1-20°C / min; Preferably, the drying is carried out under an inert atmosphere, which is preferably provided by nitrogen; Preferably, the boiling point of the solvent in the solution containing the rare earth metal precursor is lower than the boiling point of the organic matter; Preferably, at 25° C., the solubility of the solvent in the solution containing the component precursor to be loaded in 100 g of organic matter is not higher than 0.5 g; Preferably, the rare earth metal is La and / or Ce; Preferably, the amount of solution containing rare earth metal precursor is such that, based on the total amount of the catalyst, the content of the rare earth metal component is 0.3-5wt%, preferably 0.5-4wt% in terms of oxide; the content of the catalyst matrix is 95-99.7wt%, preferably 96-99.5wt%.
10. The preparation method according to any one of claims 6 to 9, wherein: In step (3), the method of removing organic matter from the product obtained in step (2) is heat treatment or vacuum desorption; Preferably, the heat treatment conditions include: heat treatment temperature of 250-500°C and time of 10-180min; Preferably, the vacuum desorption conditions include: an absolute pressure of 1×10 -4 Pa to 1Pa, temperature is 20-30℃.
11. The preparation method according to any one of claims 6 to 10, wherein: Based on the total amount of the catalyst matrix, the content of the molecular sieve is 10-65wt%, the content of the clay is 5-45wt%, and the content of the binder is 10-50wt%; Preferably, the molecular sieve is at least one of a Y-type molecular sieve, a beta molecular sieve and an MFI molecular sieve; Preferably, the molar ratio of silicon oxide to aluminum oxide in the molecular sieve is 3-80; Preferably, the clay is selected from at least one of kaolin, bentonite, montmorillonite, sepiolite and diatomaceous earth; Preferably, the binder is aluminum oxide and / or silicon oxide.
12. The preparation method according to any one of claims 6 to 11, wherein: The preparation method of the catalyst substrate comprises: The molecular sieve, clay and binder precursor are mixed, molded and calcined, and then the obtained solid product is treated with alkali; Preferably, the alkali treatment method comprises: eluting the solid product with an alkaline solution; Preferably, the alkaline solution is a non-metallic element alkaline solution, preferably ammonia water and / or ammonium salt solution; Preferably, the concentration of the alkaline solution is 0.1-10 wt %.
13. The catalytic cracking catalyst obtained by the preparation method according to any one of claims 6 to 12.
14. Use of the catalytic cracking catalyst according to any one of claims 1 to 5 and 13 in the catalytic cracking reaction of heavy oil.
Citation Information
Patent Citations
Metal passivating agents
US5001096A
Passivation of FCC catalysts
US5064524A
Value added spent fluid catalytic cracking catalyst composition and a process for preparation thereof
WO2012004806A1